2015
DOI: 10.1038/srep17001
|View full text |Cite
|
Sign up to set email alerts
|

White matter structures associated with loneliness in young adults

Abstract: Lonely individuals may exhibit dysfunction, particularly with respect to social empathy and self-efficacy. White matter (WM) structures related to loneliness have not yet been identified. We investigated the association between regional WM density (rWMD) using the UCLA Loneliness Scale in 776 healthy young students aged 18–27 years old. Loneliness scores were negatively correlated with rWMD in eight clusters: the bilateral inferior parietal lobule (IPL), right anterior insula (AI), posterior temporoparietal ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 59 publications
4
62
2
Order By: Relevance
“…Nakagawa and coworkers28 found that white matter structures relate to loneliness in young adults. Stern and colleagues33 reported that brain structure can be affected by social ties and results in more efficient use of cerebral networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakagawa and coworkers28 found that white matter structures relate to loneliness in young adults. Stern and colleagues33 reported that brain structure can be affected by social ties and results in more efficient use of cerebral networks.…”
Section: Discussionmentioning
confidence: 99%
“…UCLA-LS is a highly reliable and widely used questionnaire on social isolation loneliness28. It contains 20 items.…”
Section: Methodsmentioning
confidence: 99%
“…Benton tests, Philadelphia battery) (Gomez et al, 2015;Grossi et al, 2014;Thomas et al, 2008;Unger et al, 2016), and face memory tasks (e.g. Cambridge tests) (Gomez et al, 2015;Song et al, 2015;Unger et al, 2016); empathy was assessed by the "empathy quotient" (Chou et al, 2011;Herbet, Lafargue, Moritz-Gasser, Menjot de Champfleur, et al, 2015;Nakagawa et al, 2015;Takeuchi et al, 2013), the "interpersonal reactivity index" (Fujino et al, 2014;Parkinson & Wheatley, 2014), and the "trait emotional intelligence questionnaire" (empathy subsets) (Olszewski et al, 2017); mentalizing abilities were evaluated by "false belief" stories (Grosse Wiesmann et al, 2017), cartoon animations Scheibel et al, 2011), comic strip vignettes (Herbet et al, 2014;Kana et al, 2014), and the "reading the mind in the eyes" task (Anderson et al, 2015;Cabinio et al, 2015;Herbet et al, 2014;Mike et al, 2013;Yordanova et al, 2017). Such a wide variety of seemingly disparate disorders as well as diverse behavioral paradigms provide excellent opportunities for exploring the relationship between WM tracts and social functions.…”
Section: Methodological Summarymentioning
confidence: 99%
“…For example, Chou et al, (2011) used TBSS to examine local WM correlates of empathy ability and found that empathy quotient scores are positively correlated with FA in regional WM near social brain regions, such as the IPL and STS (see also Nakagawa et al, 2015;Takeuchi et al, 2013). Another way to accurately identify and characterize U-shaped fiber systems is to use novel fiber clustering algorithms (Zhang et al, 2014) or a sophisticated ensemble tractography approach (Takemura, Caiafa, Wandell, & Pestilli, 2016).…”
Section: Local Reginal Wm For Social Cognitionmentioning
confidence: 99%
“…Indeed, lonely persons showed weaker activation in the VS when viewing pictures of pleasant social events than when viewing pleasant social pictures of nonsocial objects . The regional white matter (WM) column in the left posterior superior temporal sulcus, the bilateral inferior parietal lobule, the right anterior insula, the posterior temporoparietal junction, the rostrolateral, and the dorsomedial prefrontal cortex have been shown to be reduced in people with high levels of perceived loneliness . It is speculated that changes in the WM volume reported above may relate to impaired empathy and low self‐efficacy.…”
Section: Introductionmentioning
confidence: 99%